1993
DOI: 10.1038/nbt0593-606
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Starch to Ethanol in a Recombinant Saccharomyces cerevisiae Strain Expressing Rice α-Amylase from a Novel Pichia pastoris Alcohol Oxidase Promoter

Abstract: A recombinant Saccharomyces cerevisiae, expressing and secreting rice alpha-amylase, converts starch to ethanol. The rice alpha-amylase gene (OS103) was placed under the transcriptional control of the promoter from a newly described Pichia pastoris alcohol oxidase genomic clone. The nucleotide sequences of ZZA1 and other methanol-regulated promoters were analyzed. A highly conserved sequence (TTG-N3-GCTTCCAA-N5-TGGT) was found in the 5' flanking regions of alcohol oxidase, methanol oxidase, and dihydroxyaceton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Of the two MREs, MRE1 exhibited strong response to methanol compared to MRE2. To date, several consensus sequences have been reported to be conserved in promoter regions of methanol-metabolizing enzyme genes from P. pastoris, H. polymorpha, and C. boidinii (7,12). Recently, the sequence responsible for methanol or both methanol and formate in C. boidnii P FDH1 were identified (6).…”
Section: Discussionmentioning
confidence: 99%
“…Of the two MREs, MRE1 exhibited strong response to methanol compared to MRE2. To date, several consensus sequences have been reported to be conserved in promoter regions of methanol-metabolizing enzyme genes from P. pastoris, H. polymorpha, and C. boidinii (7,12). Recently, the sequence responsible for methanol or both methanol and formate in C. boidnii P FDH1 were identified (6).…”
Section: Discussionmentioning
confidence: 99%
“…For differential centrifugation experiments, Western blots, and enzyme assays, protein concentrations were determined using the Pierce (Rockford, IL) bicinchoninic acid protein assay kit with bovine serum albumin as a standard. Cytosolic and pellet fractions containing 25 g of protein from differential centrifugations as well as total cellular protein from extracts were loaded onto stacked sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis (PAGE) gels for electrophoresis (29). Proteins were then transferred onto nitrocellulose using a Mini Trans-Blot electrophoretic transfer cell (Bio-Rad, Hercules, CA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Relative specific activities were indicated as a percentage of the specific activity of the wild-type (WT) strain harboring the pHWG0 vector on methanol induction medium. AOX2, region in P. pastoris alcohol oxidase II promoter hypothesized by Ohi et al (35) to be a methanol-regulatory region; K, sequence identified by Kumagai et al (29) in several promoters that is hypothesized to be a methanol-regulatory region.…”
Section: Fig 2 Mxr1 Is Necessary For Normal Accumulation Of Peroxinmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] This system contains 5?-AOX, a 942-bp fragment containing the AOX 1 promoter that allows methanol-inducible and high-level expression in P. pastoris. In addition, P. pastoris utilizes most of the post-translational modiˆcation pathway typically associated with higher eukaryotes.…”
mentioning
confidence: 99%